A Versatile Method for Viral Transfection of Calcium Indicators in the Neonatal Mouse Brain - He, Cynthia X.; Arroyo, Erica D.; Cantu, Daniel A.; Goel, Anubhuti; Portera-Cailliau, Carlos (Frontiers in Neural Circuits, 2018)
The first three postnatal weeks in rodents are a time when sensory experience drives the maturation of brain circuits, an important process that is not yet well understood. Alterations in this critical period of experience-dependent circuit assembly and plasticity contribute to several neurodevelopmental disorders, such as autism, epilepsy and schizophrenia. Therefore, techniques for recording network activity and tracing neuronal connectivity over this time period are necessary for delineating circuit refinement in typical development and how it deviates in disease. Calcium imaging with GCaMP6 and other genetically encoded indicators is rapidly becoming the preferred method for recording network activity at the single-synapse and single-cell level in vivo, especially in genetically identified neuronal populations. We describe a protocol for intracortical injection of recombinant adeno-associated viruses (rAAV) in P1 neonatal mice and demonstrate its use for longitudinal imaging of GCaMP6s in the same neurons over several weeks to characterize the developmental desynchronization of cortical network activity. Our approach is ideally suited for chronic in vivo two-photon calcium imaging of neuronal activity from synapses to entire networks during the early postnatal period.